2017
DOI: 10.1089/jayao.2016.0070
|View full text |Cite
|
Sign up to set email alerts
|

A Mindfulness-Based Intervention for Adolescents and Young Adults After Cancer Treatment: Effects on Quality of Life, Emotional Distress, and Cognitive Vulnerability

Abstract: MBI is a promising approach that is used to treat emotional distress and to improve QoL in AYAC survivors. Further research using randomized controlled trials is needed to generalize these findings. Trial registration information: www.trialregister.nl ; NTR4358.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 58 publications
1
59
1
Order By: Relevance
“…Overall, AYA used the program and responded positively to it, offering useful suggestions for improvement. This study extends the small body of research on the use of mindfulness-based programs for AYA with cancer [17], offers further support for the use of Facebook as a tool to offer social support to young people managing a health condition [36], and suggests that it may be acceptable to deliver this content through a mobile device to AYA who have experienced sarcoma.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Overall, AYA used the program and responded positively to it, offering useful suggestions for improvement. This study extends the small body of research on the use of mindfulness-based programs for AYA with cancer [17], offers further support for the use of Facebook as a tool to offer social support to young people managing a health condition [36], and suggests that it may be acceptable to deliver this content through a mobile device to AYA who have experienced sarcoma.…”
Section: Discussionsupporting
confidence: 57%
“…Sleep difficulties are common among AYA with cancer [39], so it is important to get feedback on modifications to the app that might help with sleep. Given that others have reported that mindfulness may be helpful for AYA dealing with the experience of cancer [17], the main implication from our study is that it may be feasible to deliver an MBI to AYA with sarcoma using mobile technology. Mobile-based interventions can be used to complement or extend the benefits of in-person programs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These benefits are congruent with other mindfulness-based intervention findings and self-compassion correlational studies in cancer populations. Mindfulness-based programs without a self-compassion focus have been shown to decrease anxiety and depressive symptoms(Zhang, 2015), increase overall wellbeing and quality of life, and have small but significant positive impact on biomarkers and physical health in adult cancer populations (Rouleau, Garland, & Carlson, 2015), with a recent single-arm mindfulness-based intervention showing similar promise for adolescent and young adult counterparts (Gucht et al, 2017). Research also supports that higher levels of self-compassion correlate with lower levels of stress and depression in adult cancer patients (Pinto-Gouveia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search was conducted to search for articles containing the keywords "HIV", "youth", "stress",' and "mindfulness", yielding 5 results. [1][2][3][4][5] Results regarding diagnoses other than HIV were excluded (Van der Gucht et al 1 ), leaving four primary research results which are reviewed below.…”
Section: Related Literaturementioning
confidence: 99%